Danielle Steel's Safe harbour - Gilbert, Melissa 1964-.; Johnson, Brad 1959-.; Staab, Rebecca 1961-.; Grodnik, Dan.; Swensen, Edithe; Corcoran, William; Steele, Danielle 1947-.; Newman, Joey 1976-.; New Line Home Entertainment (Firm). ([Quezon City] D'Concorde Recording Corp., 2007)
Ophélie is a grieving young widow, Matt is a heartbroken artist. Both feel as though they have lost everything until they find each other.
Based on the novel "Safe harbour" by Danielle Steel.
Videodisc release of the television movie.
Special feature: Introduction by Danielle Steel.
Title from container.
Music, Joey Newman.
Melissa Gilbert, Brad Johnson, Rebecca Staab.
Keywords: Mothers and daughters -- Drama; Loss (Psychology) -- Drama; Artists -- Drama; Mother and daughter -- Drama; San Francisco (Calif.) -- Drama; Television movies; Made-for-TV movies; Romance; Films for the hearing impaired; Drama